PL02.1.A EO2401, a novel microbiome-derived therapeutic vaccine for patients with recurrent glioblastoma: ROSALIE study. (5th September 2022) - Idbaih, A; Vieito, M; Tabatabai, G; Stradella, A; Ghiringhelli, F; Burger, M; Mildenberger, I; Fagerberg, J; Reardon, D; Wick, W
Abstract: Background: EO2401 (EO) was designed to activate existing commensal memory T-cells cross-reacting with tumor associated antigens (TAAs). EO includes microbial-derived, synthetically produced peptides corresponding to HLA-A2 restricted epitopes with molecular mimicry to three TAAs upregulated in glioblastoma (GB), IL13Rα2, BIRC5 and FOXM1, with the CD4 helper peptide UCP2 and the adjuvant Montanide. Pre-clinically EO generated strong immune responses and cross-reactive CD8 cells recognizing the targeted TAAs. Methods: This ongoing Ph 1/2 trial (NCT04116658) investigates the safety and tolerability (primary) of EO (300 µg/peptide, SC Q2W X 4, then Q4W), EO with nivolumab (3 mg/kg Q2W; EN), and EN with bevacizumab (10 mg/kg Q2W; ENB) among four Cohorts (Cs) of pts with GB at first progression/recurrence after radiotherapy/temozolomide. Treatment was delivered until progression, or 24 months. After the Ph 1 of EO followed by EN (C1), C2 investigated EN without (C2a) or with (C2b) surgery while C3 investigated ENB (population as C2a). Results: Among 40 treated pts (C1 n=3, C2a n=23, C2b n=3, C3 n=11), median age was 60 years, 53% were male, 40% had KPS 90-100%, 35% had O6-methylguanine DNA-methyltransferase promotor hypermethylated tumors, and 5% isocitrate dehydrogenase 1 mutated tumors. All evaluable pts demonstrated strong CD8 T-cell ELISPOT responses against the 3 vaccine peptides; response was shown with tetramer staining of specific CD8 in 24/25 investigated pts after in vitro stimulation and in 19/20 pts directly ex vivo. Cross-reactivity against targeted TAAs was confirmed in 20/21 pts. Majority of response were detected by week 4 after 1st dose and as early as 2 weeks in some pts. EO, EN, and ENB were well tolerated (max exposure EN 86 wks, ENB 47 wks) with EO associated toxicity limited to local administration site reactions (48%; all grade 1-2). The frequency and severity of nivolumab- or bevacizumab-associated AEs was consistent with historical single-agent profiles. With a median follow-up of 13.6 months, median progression-free survival (mPFS), and median survival for EN (C1+C2a+C2b) were 1.8 months (2 ongoing at 7.3, and 18.5 months), and 11.0 months (survival at 12 months 42%), respectively. With a median follow-up of 7.3 months (range, 3.0-10.5), pts on ENB (C3) have mPFS and survival at 6 months of 5.5 months (3 ongoing at 5.6, 7.3 and 9.1 months), and 82% (9/11 alive), respectively. ORR/DCR (ORR+SD) for EN and ENB were 10%/34% and 55%/82%, respectively. Conclusion: EO2401 generated strong systemic immune responses and was well tolerated in combination with nivolumab ± bevacizumab. Preliminary ORR/DCR and mPFS for ENB, and survival for EN seem encouraging. Updated results from the current 40 patients and results from additional 35 patients who already started treatment with EN with the option for low-dose bevacizumab edema treatment at neurological symptoms will be presented.